Discipline in the Old Testament: The Perspective of the Primeval History, Genesis 1-11 - Adutwum, Ofosu (Ghana bulletin of theology, 2007)
In the chapter of our study, we see that humankind is placed in an environment which makes it possible for it to live in relationship with God.